Business Feasibility Observation of Sweet Dried Tomato Product By SWOT Analysis at Giripurno Village, Batu City - Lilik Suprianti; Jariyah Jariyah; Endang Pudji W; Reda Rizal (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Tomato is one agricultural commodity from Batu City which is soabundant in number. Although the number of products is relativelyhigh, the benefit earned by tomato farmers is still uncertain due to pricefluctuation. The other problem is the characteristic of the tomato thateasy to get rotten. This condition increases the risk of farmers to getloss. One alternative solution to minimize the risk is processing thetomato as a sweet-dried tomato. Conversely, The sweet dried tomatoproduct is still less popular than the fruit cracker in Batu City. Throughthe community service program, we help local people to makeStrengths, Weaknesses, Opportunities, and Threats (SWOT analysis) tosee the prospect of sweet-dried tomatoes. We also recommended somestrategies for developing the sweet-dried tomatoes business to thevillage authority.